The river - Paulsen, Gary. (New York : Dell Laurel-Leaf, 1998)
Because of his success surviving alone in the wilderness for fifty-four days, fifteen-year-old Brian, profoundly changed by his time in the wild, is asked to undergo a similar experience to help scientists learn more about the psychology of survival.
Booklist starred.
School Library Journal.
Wilson's Junior High School.
6.3
5-8
Keywords: Self-reliance -- Fiction; Survival -- Fiction; Self-reliance -- Fiction; Survival skills -- Fiction